FRACTURES OF THE LOWER THORACIC AND LUMBAR SPINE - Mardonov Jamshid Jahongirovich,; Karomov Suhrob Mirmuhsinovich, (TADQIQOTLAR, 2025)
ABSTRACT. Fractures of the lower thoracic (T10–T12) and lumbar (L1–L5) spine  are  common  injuries  resulting  from  high-energy  trauma,  such  as  road  traffic accidents, falls from height, or sports-related incidents. These fractures may involve vertebral  body  compression,  burst  fractures,  or  fracture-dislocations,  often accompanied by neurological deficits. Accurate diagnosis, classification, and timely management  are  essential  to  prevent  long-term  disability.  This  article  reviews  the epidemiology,  mechanisms of injury, classification systems, diagnostic approaches, and current treatment strategies for lower thoracic and lumbar spine fractures.